MEDIA TEKNOLOGI DAN GLOBALISASI: SINTESIS TEORETIS DALAM MEMAHAMI TRANSFORMASI SOSIAL GLOBAL - Asriadi, Asriadi; Ismawati; Asmawati (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2026)
The development of media and communication technology has become a crucial factor driving the process of globalization and influencing changes in the social, cultural, political, and economic structures of global society. This article aims to analyze the relationship between media, technology, and globalization through four theoretical perspectives: technological determinism, cultural determinism, cultural imperialism, and post-colonialism in the formation of global identity. This study demonstrates that communication technology plays a significant role in shaping patterns of social interaction, but its interpretation remains influenced by the social and cultural context. In the current of media globalization, the dominance of Western culture through the global media industry is often understood as a form of cultural imperialism, although global dynamics also show the emergence of influences from non-Western countries. A post-colonial approach is used to critique the inequality of representation and power relations within the global media system. The study's findings indicate that media globalization produces a hybrid cultural identity, a blend of local and global elements, and opens up space for identity negotiation and resistance to the dominance of certain cultures. Therefore, a critical understanding of the relationship between media, technology, and globalization is crucial in interpreting the dynamics of global communication in the digital era.